Characteristics of autism spectrum disorders in a sample of egyptian and saudi patients: transcultural cross sectional study - Hussein Hanan; Taha Ghada RA; Almanasef Afrah (BMC, 2011)
Abstract Background Autism is a biological disorder with clearly defined phenomenology. Studies from the Middle East on this topic have been particularly rare. Little is known about the influence of culture on clinical features, presentations and management of autism. The current study was done to compare characteristics of autism in two groups of Egyptian as well as Saudi children. Methods The sample included 48 children with Autism Spectrum Disorder. They were recruited from the Okasha Institute of Psychiatry, Ain Shams University, Cairo, Egypt and Al-Amal Complex for Mental Health, Dammam, Kingdom of Saudi Arabia. They were grouped into an Egyptian group (n = 20) and a Saudi group (n = 28). They were assessed both clinically and psychometrically using the GARS, the Vineland adaptive behavioral scale, and the Stanford Binnet IQ test. Results Typical autism was more prevalent than atypical autism in both groups. There were no statistically significant differences in clinical variables like regression, hyperactivity, epilepsy or mental retardation. Delayed language development was significantly higher in the Egyptian group while delay in all developmental milestones was more significant in the Saudi group. The Vineland communication subscale showed more significant severe and profound communication defects in the Saudi group while the Gilliam developmental subscale showed significantly more average scores in the Egyptian group. Both groups differed significantly such that the age of noticing abnormality was younger in the Saudi group. The age at diagnosis and at the commencement of intervention was lower in the Egyptian group. The Saudi group showed a higher percentage of missing examinations, older birth order and significantly higher preference to drug treatment, while the Egyptian group showed a high preference to behavioral and phoniatric therapies, higher paternal and maternal education, higher employment among parents and higher family concern. Conclusion Cultural context may significantly influence the age of noticing abnormality, the age of starting intervention, developmental and perinatal problems, family concerns about managing the problem as well as familial tendency for neurodevelopmental disorders, all of which have important impact on clinical symptomatology and severity of autism. Culture also influences significantly the ways of investigating and treating autism.